(untitled)
The aim of the study was to evaluate and compare the clinical characteristics of COVID-19 infection in children and adult. This observational cross-sectional study was conducted in multiple corona dedicated hospitals, situated in Dhaka, Bangladesh from April 2020 to January 2021. Data of COVID -19 positive hospitalized patients were collected in a pre-tested question- naire during hospital stay with proper protective measures. Clinical characteristics of the COVID-19 positive hospitalized children and adult patients were evaluated. Approval was taken from institutional review board of respective institutes. Statistical analyses of the results were obtained by using SPSS-25. In this study the male-to-female ratio was 1:1.6 and 2.8:1 in child and adult patients respectively. More than three quarter (75.4%) of subjects had family members affected before the illness in the child group and more than half (50.9%) cases in the adult group. History of contact or exposure with any symptomatic case was present in 61.4% cases in the adult group but only 14% in the child group. The mean duration of illness was less (9.1